(untitled) (MAUSAM, 1998)
The cyclone cluster that formed over the Bay of Bengal during November 1992 has been looked into in relation to sea surface temperature (SST) distribution obtained from long. 1°x1° grid averages remotely sensed by NOAA-AVHRR. Examination of weekly SSTs has revealed that entire Bay of Bengal north of 8°N was unusually warmer about a week before the foundation of the cyclone cluster. As a matter of fact, during the above period the SST for each of the 60 grids over the sea area between 13°- 21° and 81°- 90°E exceeded 30°C. Widespread cooling of the sea was noticed just before the commencement of cyclogenesis.